Stochastic programming model based on synthesizing effect function - Lei Zhou; Fa-Chao Li (2009 International Conference on Machine Learning and Cybernetics, 2009)
In this paper, based on the stochastic optimization theory, we add synthesizing effect constraint condition to stochastic programming model. Through synthesizing effect constraint of expectation and variance, we establish a kind of stochastic programming model which has guiding significance. We also show that under certain condition, this new model is a convex programming, and prove that if the independent random variables are the normal distribution, the stochastic programming model with synthesizing effect function constraints is equivalent to chance constrained programming model. Last, we get the algorithm of this model.